Predictive factors of bowel necrosis in patients with incarcerated femoral hernia - Beji, H.; Bouassida, M.; Chtourou, M. F.; Zribi, S.; Laamiri, G.; Kallel, Y.; Mroua, B.; Mighri, M. M.; Touinsi, H. (Hernia : the journal of hernias and abdominal wall surgery, 2023)
Purpose Intestinal necrosis is a frequent complication in patients with incarcerated femoral hernias (IFH). Knowing the low incidence of IFH, few series with large samples studied predictive factors of intestinal necrosis. The main objectives of our study were to determine the predictive preoperative factors of intestinal necrosis in patients with IFH and to compare its morbidity with that related to incarcerate inguinal hernias (IIH). Methods We conducted a retrospective observational cohort study in which we included patients with incarcerated groin hernias (IGH). This is a single-center study between January 2004 and December 2021. Patients were divided into two groups: group A (admitted for IFH) and group B (admitted for IIH). Intestinal necrosis was confirmed intraoperatively. Results 383 patients with IGH were included in the study: 91 patients had IFH (23.76%) and 282 patients had IIH (76.24%). In patients with IFH, the median age was 67 years. We had 60 females (66%) and 31 males (34%). Bowel ischemia was present in 29 patients (32%). Bowel necrosis was present in 14 patients (16%). We identified three independent variables predicting bowel necrosis in patients with IFH: Duration from symptoms to surgery, NLR (Neutrophil to Lymphocyte ratio), and urea. Bowel ischemia and bowel necrosis were significantly higher in patients with IFH compared to those with IIH. Conclusions In summary, we found that duration from symptoms to surgery, NLR, and urea were significantly predictive of intestinal necrosis in patients with IFH.